Analysis of Promising Approaches to COVID-19 Vaccine Development - G. G. Onishchenko; T. E. Sizikova; V. N. Lebedev; S. V. Borisevich (Биопрепараты: Профилактика, диагностика, лечение, 2020)
The number of confirmed COVID-19 cases worldwide amounted to 50 million at the beginning of November 2020. This is clearly not enough for the formation of herd immunity, which will prevent repeated outbreaks of the disease. Quarantine measures can only curb the spread of the disease to some extent, therefore specific preventive measures are needed to create collective immunity to COVID-19.The underlying principle of collective immunity is indirect protection of the whole of the population by immunising a certain part of it. Vaccination is the most effective approach to prevention of epidemic outbreaks. The aim of the study was to analyse promising approaches to the development of vaccines against novel coronavirus COVID-19 infection. The paper summarises data on development studies and clinical trials of COVID-19 vaccines conducted in different countries. It analyses the pros and cons of different platforms for vaccine development (attenuated vaccines, inactivated vaccines, subunit vaccines, DNA and RNA vaccines, recombinant vector vaccines). The paper presents a potential design of novel vaccines. It was concluded that COVID-19 vaccines might be developed both for immunising high-risk groups and for mass immunisation. An optimal solution for the second task would be to develop human or monkey adenovirus vector-based vaccines whose mass production has already been unveiled.